The Impact of Vision Loss on Allocentric Spatial Coding - Martolini, Chiara; Cappagli, Giulia; Luparia, Antonella; Signorini, Sabrina; Gori, Monica (Frontiers in Neuroscience, 2020)
Several works have demonstrated that visual experience plays a critical role in the development of allocentric spatial coding. Indeed, while children with a typical development start to code space by relying on allocentric landmarks from the first year of life, blind children remain anchored to an egocentric perspective until late adolescence. Nonetheless, little is known about when and how visually impaired children acquire the ability to switch from an egocentric to an allocentric frame of reference across childhood. This work aims to investigate whether visual experience is necessary to shift from bodily to external frames of reference. Children with low vision and sighted controls between 4 and 9 years of age were asked to solve a visual Switching-Perspective task requiring them to assume an egocentric or an allocentric perspective depending on the task condition. We hypothesize that, if visual experience is necessary for allocentric spatial coding, then low vision children would have been impaired to switch from egocentric to allocentric perspectives. Results support this hypothesis, confirming a developmental delay in the ability to update spatial coordinates in low vision children. It suggests a pivotal role of vision in shaping allocentric spatial coding across development.